History of U.S Economic Support for Pakistan 1950-88 - Faiz , Muhammad Aslam; Imran, Muhammad; Shah, Naveed Ali (Pakistan Journal of Humanities and Social Sciences, 2023)
On August 14, 1947, Pakistan was officially established. Pakistan has maintained friendly relations with the United States ever since it gained independence. However, after that, the relations were like a game of hide and seek; they went from harmony to discord and back again, alternating back and forth between the two states. The researcher has made an effort, based on the primary topic of research that they have been working on, to chronically enlist the important events, agreements, and coordinations that have occurred between the two countries. The primary focus is on the economic aid that was provided by the United States to Pakistan, which brought this region to the forefront of attention in the wake of regional stability. The United States of America refashioned its relations with Pakistan in order to achieve certain personal motivations. Following a thorough examination of the pertinent published material, the researcher arrived at the upbeat and optimistic conclusion that the bilateral ties between the two nations will continue to improve in the years to come.